A split-face randomized controlled trial of treatment with broadband light for enlarged facial pores. (3rd October 2021) - Yu, Wenxin; Han, Yue; Wu, Xianglei; Shang, Ying; Ying, Hnaru; Ma, Gang; Liu, Ying; Lin, Xiaoxi
Abstract: Background: Broadband light (BBL) is one of the intense pulsed light. BBL treatment for nonablative, noninvasive skin tightening and rejuvenation reportedly elicits satisfactory clinical outcomes. Up until now, self-controlled case series with objective evaluation of efficacy of facial pores in response to BBL treatment have not been reported. We aimed to assess its safety and efficacy on enlarged facial pores by objective measuring technique. Objective: To evaluate the efficacy and safety of BBL on the appearance of facial pores. Methods: 25 patients received five treatments with BBL at 2-week intervals. One split-face was treated by BBL, another split-face was untreated as a control. Objective measurements of the quantitative number of pores were calculated with a VISIA-CR imaging system. Skin elasticity, transepidermal water loss, skin sebum excretion, and skin surface hydration values were also evaluated by using an Elastimeter, Vapometer, Sebumscale, and Moisturemeter. Results: Pretreatment, the total average number of facial pores was 835.88 and 835.68 for BBL-treated facial sides and untreated facial sides, respectively ( p  = .993). These values were 801.44 and 811.8, respectively, 2 months after the final treatment ( p  = .606). There were no long-term side effects. Conclusion: BBL seems to be a safe and mildly effective approach to reduce detectable pores.